Mechatronic hands : prosthetic and robotic design - Chappell, Paul H. (IET control, robotics and sensors series, 2016)
This book describes the technical design characteristics of the main components that go into forming an artificial hand whether it is a simple design that does not have a natural appearance or a more complicated design where there are multiple movements of the fingers and thumb.